Forecasting model to predict the first occurrence of Scaphoideus titanus nymphal stages in selected locations in Austria - Kerstin Kolkmann; Gudrun Strauss; Josef Eitzinger; Sylvia Blümel (Journal of Central European Agriculture)
Scaphoideus titanus Ball, 1932 (Hemiptera: Cicadellidae) is the main vector of Grapevine flavescence dorée phytoplasma (FDp), causing the economically important grapevine yellows disease flavescence dorée in Europe. Effective management of this disease relies on vector control and the uprooting of infected grapevines. By controlling the S. titanus third nymphal stage (N3), the spread of FDp can be prevented. In Austria, yearly monitoring of S. titanus nymphs in different wine-growing regions is necessary to determine the best time for control. The recent phenology changes of S. titanus make monitoring scheduling more difficult and propose the use of an accurate forecasting model. The present study aimed to test existing forecasting models for their accuracy and applicability to predict the first seasonal occurrence of the first nymphal stage (N1) of S. titanus and to develop new prediction models for N1 and N3 in Austria for the first time. Monitoring data from 2013 to 2020 from six different wine-growing areas in Austria were analysed. The existing forecasting models examined in this study predicted the first seasonal occurrence of N1 on average 3.3 days too early or 5.8 days too late, whereas the newly developed multiple linear regression model (MLR) for N1 predicted the first seasonal occurrence on average 3.4 days too early. The newly developed model for N3 predicted the first occurrence on average 6.6 days too early. To continuously improve the multiple linear regression models additional datasets, in particular from years with extreme weather events, should be included in the analysis.